GRAMMATICAL COHESIVE DEVICES IN JOKO WIDODO’S SPEECH TEXT - TAFULI, YOHANA KRISTA EKA; BUSTAN, FRANSISKUS; HAAN, JOHN W (Postgraduate School, Universitas Nusa Cendana, 2023)
Speech is an example of expressive discourse. Speech is an interesting object of study because speech is a unit of language that contains meaning and is composed of a series of sentences, diction, and grammatical, also contextual relations. The study of written and spoken discourse consists of cohesion and coherence. This research, therefore, is designed to the researcher can identify and describe the characteristics of grammatical cohesive devices in Joko Widodo’s Speech Text at the G-20 Sessions on November 15, 2022. A descriptive method is employed in this research and data obtained were analyzed qualitatively through identification and classification. The technique used for data collection is the study of Literature and the Listen-Note Technique. The result shows that Grammatical cohesive devices include referents, substitutions, ellipsis, and conjunctions. Based on the results of an analysis of Joko Widodo's speech at the G-20 Summit, it appears that all grammatical cohesive tools are used, although in different proportions. The grammatical cohesion that seems to dominate is a reference, followed by a conjunction, substitution, and ellipsis.